Modelos de Investimento: Metodologia e Resultados - Casagrande, Elton Eustáquio [UNESP] (Editora 34, 2020)
This paper provides an overview of the empirical studies on corporate financing patterns and firm’s investment behavior. In a frictionless world the Modigliani-Miller theorem holds as well as the neoclassical investment theory. However, in presence of imperfections resulting from information asymmetries internal finance is often less costly than external finance. The goal in this article is to show how empirical studies have examined the role of financial constraints and firm’s investment behavior.

Este artigo fornece uma visão geral dos estudos empíricos sobre padrões de financiamento corporativo e comportamento de investimento da empresa. Em um mundo sem atrito, o teorema de Modigliani-Miller é válido, assim como a teoria do investimento neoclássico. No entanto, na presença de imperfeições resultantes de assimetrias de informação, o financiamento interno costuma ser menos oneroso do que o financiamento externo. O objetivo deste artigo é mostrar como os estudos empíricos examinaram o papel das restrições financeiras e o comportamento do investimento da empresa.
Investment Models: Methodology and Results
Keywords: Investment; asymmetry; liquidity; financing; Investimento; assimetria; liquidez; financiamento